Analysis of the significance of the marketing mix in e-commerce - Kostić Radan; Savić Aleksandar; Mihajlović Milan (Megatrend Revija, 2022)
Internet marketing is a new philosophy and an interesting topic especially for researchers in the field of marketing. It is a new way of marketing a product / service globally in a target market around the world. This paper presents a new approach to understanding the role of the marketing mix in e-commerce. The importance of marketing in e-commerce is often accompanied by problems with the application of common marketing tools in a virtual environment. The paper identifies elements of the marketing mix in e-commerce in line with the trend of e-commerce and Internet technology. The aim of this paper is to point out the role of marketing mix in e-commerce by applying the 7P model that enables the structuring of changes in terms of trade and information services of online stores.